COMPARISON STUDY OF INSTALLATION COSTS OF CONCRETE CULVERT TO MODULAR WELLS FROM POLYPROPYLENE PANEL - Nuh, Syafarudin M.; Michelim, Albert Stanley (Jurnal Teknik Sipil, 2023)
Pontianak City has a low ground elevation and a reasonably high groundwater level. The distribution of clean water from regional companies tends to be less than optimal, and there is high rainwater runoff, causing the channel discharge to increase along with the growth of land converted into residential and business areas. Therefore, houses often use fresh water storage, both raw and rainwater, to meet clean water needs. One type that is often used is concrete culverts. However, concrete culverts have gaps in the joints that have the potential to contaminate storage water. The development of modular wells can be an option that is superior in various aspects to concrete culverts. The results showed that installing polypropylene modular wells costs less than concrete culvert wells. In addition, the use of modular wells also has advantages in terms of ease of installation and maintenance, as well as efficiency in land use. Endurance strength Modular wells can carry a load of up to 24 tons/m2. Thus, the results of this study are expected to provide alternative methods of storing clean water in Pontianak City that are more effective and efficient in terms of cost and quality by considering technical and environmental factors.